Design and development of the solar cycloidal thermal concentrator and tapered receiver assembly along with theoretical evaluation of system performance - Kulkarni, Mohan; Dingare, Sunil; Kulkarni, Chandrakant (Frontiers in Mechanical Engineering, 2023)
In this paper, the design and development of a solar cycloidal concentrating system along with utilization of the tapered receiver is presented. For the determination of the performance of the system, theoretical analysis was carried out. The novel concept of utilizing a tapered receiver for a solar cycloidal concentrating system is an innovative approach for this research. After the determination of various parameters for this system, a patent was filed and published under the patent No. 202021028009A on 31 July 2020. For the comparative study purpose, the author has taken three receivers with a constant concentration ratio and different diameters such as .038 m, .031 m, and .025 m. Theoretical evaluation of the system is estimated using modes of heat transfers and using the relation of energy balance. Various correlations are determined for an analytical evaluation purpose. By using graphical collation of all the results for all the three receivers, the author has proposed to use a tapered receiver with the variable CR. CR denotes the concentration ratio. A concentration ratio is defined as the ratio of the area of an aperture to the area of a receiver. In this research, a variable concentration ratio (CR) is used. The receiver used has a diameter which reduces from the inlet to the outlet, and hence, the intercept factor decreases and the concentration ratio increases, leading to an enhancement in efficiency.